Diabetes and Ramadan: Practical guidelines. (April 2017) - Hassanein, Mohamed; Al-Arouj, Monira; Hamdy, Osama; Bebakar, Wan Mohamad Wan; Jabbar, Abdul; Al-Madani, Abdulrazzaq; Hanif, Wasim; Lessan, Nader; Basit, Abdul; Tayeb, Khaled; Omar, MAK; Abdallah, Khalifa; et al.
Abstract: Ramadan fasting is one of the five pillars of Islam and is compulsory for all healthy Muslims from puberty onwards. Exemptions exist for people with serious medical conditions, including many with diabetes, but a large number will participate, often against medical advice. Ensuring the optimal care of these patients during Ramadan is crucial. The International Diabetes Federation (IDF) and Diabetes and Ramadan (DAR) International Alliance have come together to deliver comprehensive guidelines on this subject. The key areas covered include epidemiology, the physiology of fasting, risk stratification, nutrition advice and medication adjustment. The IDF-DAR Practical Guidelines should enhance knowledge surrounding the issue of diabetes and Ramadan fasting, thereby empowering healthcare professionals to give the most up-to-date advice and the best possible support to their patients during Ramadan.